Short Term Outcome & Surgical Risk of Patients Undergoing Mitral Valve Repair vs Replacement in Severe Ischemic Mitral Regurgitation - Abd Raboh, Ashraf Mostafa; Zikri, Magued Abdelmessih; Seoud Ibrahim, Diaa Eldin Aboul; Abdelaal, Amr Mahmmoud; Abdelmesseh, John Malaty Fouad (Journal of Neonatal Surgery, 2025)
Background: Although severe ischemic mitral regurgitation, commonly occurring after myocardial infarction and associated with high mortality, often necessitates surgical intervention, the short-term outcome and surgical risk of patients undergoing mitral valve repair versus replacement remain uncertain, warranting comparison during concomitant coronary artery bypass grafting to assess their impact on morbidity, neurological recovery, and survival. This study aimed to compare early surgical outcomes of mitral valve repair versus replacement with concomitant coronary artery bypass grafting (CABG) and analyze the impact on morbidity, neurological recovery and short-term survival. Subjects and methods: In the period between March 2023 and June 2024, 100 patients (77% males, 23% females) were conducted in this study. 37 males (74%) and 13 females (26%) in group A compared to 40 males (80%) and 10 (20%) females in group B. Mean age was 59.74 ± 11.04 in group A, while that in group B was 56.88 ± 9.84 years old. The patients included in this research were CABG patients having severe ischemic mitral regurgitation & underwent surgery for MV (repair or replacement) at Kasr Al-Ainy Hospital and other affiliated hospitals. Clinical and imaging data were prospectively evaluated. Patients were divided into 2 groups depending on the procedure, group A (the repair group) & group B (the replacement group). Result: Postoperative residual MR occurred in 21% of patients, more frequently in group A (repair, 34%) than in group B (replacement, 8%) (P=0.001), making repair a predictor of postoperative MR. Patients with residual MR had more preoperative MV morphology abnormalities (P=0.015). Multivariable analysis confirmed preoperative MV abnormalities and repair technique as independent predictors (P=0.015, P=0.001). Intraoperative TEE showed more significant MR in group A (P=0.027). Subvalvular apparatus preservation had no statistical significance (P=1). Postoperative MR did not significantly affect EF, renal, or neurological outcomes (GCS: 13.68 ± 2.09 vs. 13.50 ± 2.64; P>0.05). Mitral valve replacement was linked to higher rates of postoperative AF (P=0.001) and increased in-hospital mortality (P=0.046). Conclusion: Mitral valve replacement is a suitable option for patients with chronic ischemic mitral regurgitation and impaired left ventricular function (over mitral valve repair). It provides better results in terms of freedom from reoperation with comparable valve-related complication rates. Although postoperative residual MR was not associated with significant morbidity and postoperative complications, significant impairment in mid-term survival could not be confirmed by the data